Evaluation of lighting systems and energy audit building information engineering malikussaleh university - Novra, Novra; Multazam, Teuku; Nasution, Fakhruddin Ahmad; Muhammad, Muhammad (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
Technology that is developing today, the use of electrical energy is a major concern in supporting energy consumption intensity programs conducted by the government. This study aims to analyze the level of lighting and energy consumption in the building of Information Engineering Malikussaleh University. this study was conducted to evaluate the building lighting based on SNI standard 03-6575-2001 and calculate the energy consumption intensity value (IKE) of the building. The results showed that the level of lighting in this building has not met the minimum standards, which is caused by several factors, such as suboptimal lighting design, inappropriate lamp types, age and maintenance of the lighting system, and the influence of the physical environment of the building. However, the Ike value of the building is classified as very efficient, which is equal to 6.24 kWh/m2/year. Based on the results of the study, detailed data on the level of lighting and energy consumption were obtained, allowing a better evaluation of the energy efficiency of the building. Implementation of the results of this study is expected to be the basis for improved lighting system design to improve energy efficiency and overall user comfort of the building..